Nest Predation Pressure Differs Between Urban Ground- and Hole-Nesting Birds: Evidence from a Multi-Year Artificial Nest Predation Experiment - Jukka Jokimäki; Marja-Liisa Kaisanlahti-Jokimäki (Birds, 2025)
Urbanization changes the environment through physical constructions, disturbances, and altered resource availability. These modifications influence both prey and predator assemblages. Several studies have indicated that hole-nesting birds outnumber ground nesters in cities. Differential nest predation can be one reason behind this observation. We conducted a multi-year artificial nest predation experiment along an urban gradient by using artificial ground nests and nestboxes in Rovaniemi, Finland. Because visually searching avian predators dominate in cities, we predicted that nest predation of ground nests will increase with urbanization, whereas nests in holes will be better protected than ground nests. Ground nest predation increased with urbanization, being lowest in forest and rural areas, intermediate in suburban area and highest in urban area. However, there was no year-effects on artificial ground nest predation, suggesting that even a single-year results of artificial nest predation experiment can be reliable. In the city, ground nest predation was greater than nestbox predation. In forests, nestbox predation was greater than ground nest predation. Among ground nests, predation was greater in the city than in forests. Among nestboxes, predation was greater in forest than in urban or suburban habitats. Only the ground nest predation was greater in managed than in un-managed parks. Ground nest predation decreased with tree cover and increased with the patch area. No variables were entered in the models of the nestboxes. The results indicated that ground nesters might avoid urban areas as nesting sites. We assume that visually searching avian predators benefit from the lack of covering vegetation in city parks. However, because most avian nest predators, like corvids, are not effective nest predators of hole-nesting birds, urban areas are safe nesting areas for hole-nesters. The results suggest that nest predation is one important factor that could explain, why hole-nesting bird species outnumbered ...